Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Pada Haluan Kopi di Kota Surakarta - Nur Annisa Triahartari; Raden Kunto Adi (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2024)
Increasing coffee consumption in Indonesia is a big opportunity for businesspeople in the coffee sector, such as coffee shops. This opportunity has caused an increase in coffee shop numbers, including in Surakarta. Increasing competition means that businesspeople must make various innovations, both in the foods and drinks offered and the comfort of the place. This research aims to determine the factors influencing purchasing decisions at Haluan Kopi in Surakarta City. The basic methods used in this research are descriptive and survey methods. The research location was determined purposively, and the sample was taken using a purposive sampling method with 100 Haluan Kopi consumers as respondents. Data collection techniques include questionnaires, interviews, recording, and documentation. The data analysis method uses multiple linear regression analysis, F test, coefficient of determination, and significance tests. The results show that the average respondent is male, and most respondents are aged 17-25, with at least a high school/vocational education. Most respondents earn IDR 1,800,000.00-IDR 3,000,000.00; the average respondent is a student. The variables of electronic word of mouth, product quality, and service quality have a positive influence on purchasing decisions at Haluan Kopi in Surakarta City. In contrast, the individual social media, price, and store atmosphere variables do not significantly influence purchasing decisions at Haluan Kopi in Surakarta City. The variables of social media, electronic word of mouth, price, product quality, service quality, and store atmosphere positively influence purchasing decisions at Haluan Kopi in Surakarta City.